Residual antibiotics in milk samples: Assessing the risk and prevalence in Bangladesh - Farhana Rinky; Asma Rahman; Sompa Reza; Abira Nowar; Sharmin Rumi Alim (Heliyon)
The study aimed to analyze five commonly used veterinary antibiotics: tetracycline (TC), oxytetracycline (OTC), doxycycline (DOX), chlortetracycline (CTC), and enrofloxacin (ENR) in different types of milk samples, risk estimation, and to investigate the correlation between the presence of multiple antibiotic residues. About 27 milk samples, such as raw milk from collection centers, processed milk from processing plants, pasteurized, UHT, and flavored milk from retail stores, were examined using RP-HPLC against five veterinary antibiotics in Dhaka, Bangladesh. The correlation between antibiotics was analyzed using Pearson's correlation test. OTC was prevalent in 100 % of the analyzed samples, while CTC, ENR, TC, and DOX were found in 29.63 %, 22.22 %, 18.52 %, and 7.41 % of the samples, respectively. Only OTC residues were detected in both raw and soon-after-processed milk. However, most of the UHT and flavored milk samples showed the occurrence of multiple antibiotic residues. Among the detected samples, 37.04 % exceeded the MRLs, while 44.44 % were near the limit. The mean concentration of TC was higher than others. The correlation test revealed a significant moderate to strong positive correlation between TC, CTC, DOX, and ENR, while OTC showed no significant correlation with the other antibiotics. Risk analysis showed no immediate risk from detected antibiotics but can raise concern due to continuous exposure. The results obtained from this study underscore the importance of adhering to appropriate withdrawal periods and implementing appropriate quality control protocols to ensure the protection of public health.